2021
DOI: 10.1177/00914509211002542
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Drug Consumption Room Policy and Progress in Finland

Abstract: Drug consumption rooms (DCRs) have been established to reach high-risk people who use drugs (PWUDs) and reduce drug-associated harm. Despite effectiveness, their establishment requires strong advocacy and efforts since moral perspectives tend to prevail over health outcomes in many countries. DCRs have generally emerged as a local response to inadequate central government policy. Likewise, the initiative of the Municipality of Helsinki in 2018 opened up a discussion between central government, society, and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Enabling new measures in the prevention of drug deaths creates a challenge to the current criminal control policy. For example, recently, the City of Helsinki began an initiative to establish a drug consumption room in its area, but no action has been taken since the Criminal Code was seen to be an obstacle (Unlu et al 2021). The same obstacle was met in a project known from some other countries (e.g.…”
Section: Retreat: a Redistribution Of Labour Between Social And Health Care And Criminal Control Policymentioning
confidence: 99%
“…Enabling new measures in the prevention of drug deaths creates a challenge to the current criminal control policy. For example, recently, the City of Helsinki began an initiative to establish a drug consumption room in its area, but no action has been taken since the Criminal Code was seen to be an obstacle (Unlu et al 2021). The same obstacle was met in a project known from some other countries (e.g.…”
Section: Retreat: a Redistribution Of Labour Between Social And Health Care And Criminal Control Policymentioning
confidence: 99%
“…Recent research has identified a range of challenges in establishing DCRs in areas where they have been proposed. These include insufficient political leadership [ 20 , 21 ]; community concerns over neighbourhood impacts [ 22 , 23 ]; public scepticism as to their value [ 24 ]; the impact of language and nomenclature [ 25 , 26 ]; and potential legal barriers [ 19 ]. The perceived policy goals of DCRs also vary.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing research on public and political attitudes to DCRs, which seeks to better understand the barriers and enablers to their implementation in a range of contexts [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. This paper explores the views and experiences of key strategic decision-makers who, were DCRs to be introduced in Scotland, would likely be involved in their implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Several countries have implemented decriminalization approaches for illicit drug use, which vary widely in design and operations. 3 , 4 But beyond these variations, and while many Canadians agree with the general concept of “decriminalization” of illicit drug use, decriminalization is a complex construct with potential for multiple—some hidden—pitfalls or unintended adverse consequences. Some of these have been considered previously within cannabis policy reform debates (but were mostly avoided in Canada by opting for legalization and regulation of cannabis).…”
mentioning
confidence: 99%
“…Third, many criminal justice-initiated alternatives to punishment involve institutionalized “discretion,” for example, by police or prosecutors, as to whether diversion approaches should be used. 4 , 5 These decisions rely on mostly subjective judgements of individual or behavioural characteristics of the offender, while in practice commonly translate into expressions of socio-racial biases, stigma, or outright discrimination. While many justice system authorities prefer to use punitive over alternative or “soft” approaches, almost any user of illicit drugs may indicate some (subjective) reason possibly viewed as a possible “public safety” threat.…”
mentioning
confidence: 99%